2019
DOI: 10.1088/1742-6596/1266/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Numerical Analysis of Hydropower Tunnel in Lesser Himalayan Region of Nepal- A Case Study

Abstract: This paper is focused on the assessment and numerical analysis of hydropower tunnel of the Lesser Himalayan Region of Nepal. This region lies between two major faults namely Main Boundary Thrust (MBT) and the Main Central Thrust (MCT) with weak rock mass like phyllite, schist, gneiss, phyllitic schist, etc. Thus, to overcome the stability problems during underground construction, proper rock support system must be installed. Rock mass classification systems are commonly used for estimating the rock support sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The design follows the guidelines laid out in the AASHTO LRFD 2012 Bridge Design Code and takes into account a hypothetical building timeline. 15,[32][33][34][37][38][39] F I G U R E 3 Construction sequence top-down method. 32,33 TUNNEL SECTION GEOMETRY Reinforced concrete was used in the tunnel's construction to make it a strong, long-lasting structure.…”
Section: Methods Of Constructionmentioning
confidence: 99%
“…The design follows the guidelines laid out in the AASHTO LRFD 2012 Bridge Design Code and takes into account a hypothetical building timeline. 15,[32][33][34][37][38][39] F I G U R E 3 Construction sequence top-down method. 32,33 TUNNEL SECTION GEOMETRY Reinforced concrete was used in the tunnel's construction to make it a strong, long-lasting structure.…”
Section: Methods Of Constructionmentioning
confidence: 99%
“…Khadka et.al. (2019) have suggested that the rock mass classification approach is not adequate for design and estimation of tunnel support in the Lesser Himalayan Region of Nepal [9].…”
Section: Static Design Of Tunnel Practice In Nepalmentioning
confidence: 99%
“…The support was seen as inadequate for the moment of Rock class III and Rock class IV. Khadka [13] analyzed the rock mass in terms of good and poor rock separately. He has recommended that when the elastic-plastic model is used, residual parameters are not required for the extremely weak rocks (GSI value less than 30).…”
Section: Rock Mass Propertiesmentioning
confidence: 99%
“…Due to the fact that Nepal stretches along the Greater Himalayas and is situated close to the collisional boundary between the Indian and Eurasian plates, there is a notable risk of a major earthquake occurring in this region [1]. Nepal is characterized by three major fault systems: the Main Central Thrust (MCT), Main Boundary Thrust (MBT), and Himalayan Frontal Thrust (HFT), alongside numerous smaller faults, totaling 92, running throughout the country's limited width [2][3][4]. The Kathmandu Valley's peak ground acceleration (PGA) variation was calculated to be between 0.4 and 0.55 g [5] and the PGA of the Banepa&Dhulikhel area was calculated between 0.29 and 0.35 g for bedrock and 0.46 to 0.55 g for free field [6].…”
Section: Introductionmentioning
confidence: 99%